2020
DOI: 10.1097/qai.0000000000002462
|View full text |Cite
|
Sign up to set email alerts
|

Physical Distancing Due to COVID-19 Disrupts Sexual Behaviors Among Gay and Bisexual Men in Australia: Implications for Trends in HIV and Other Sexually Transmissible Infections

Abstract: Introduction: In March 2020, Australian state and federal governments introduced physical distancing measures alongside widespread testing to combat COVID-19. These measures may decrease people's sexual contacts and thus reduce the transmission of HIV and other sexually transmissible infections (STIs). We investigated the impact of physical distancing measures due to COVID-19 on the sexual behavior of gay and bisexual men in Australia. Methods: Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 20 publications
14
124
0
Order By: Relevance
“…This is in line with studies in the USA and Australia where MSM indicated fewer sexual partners or having less opportunities for having sex. [17][18][19] The reduced sexual activities with sexual partners outside the household is likely to result in reduced HIV and STI transmission among MSM. Among those who had sex with non-steady partners during the lockdown in our study, more than two-third were using PrEP or were HIV positive.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with studies in the USA and Australia where MSM indicated fewer sexual partners or having less opportunities for having sex. [17][18][19] The reduced sexual activities with sexual partners outside the household is likely to result in reduced HIV and STI transmission among MSM. Among those who had sex with non-steady partners during the lockdown in our study, more than two-third were using PrEP or were HIV positive.…”
Section: Discussionmentioning
confidence: 99%
“…104,105 Other studies (but not all) have described substantial reductions in sex with non-steady partners during the first weeks of lockdown among men who have sex with men (MSM). [106][107][108][109] These studies describe MSM as indicating fewer sexual partners or fewer opportunities for having sex. Reduced sexual activity with sexual partners external to the household is more likely to result in reduced sexual transmitted infections among HIV-positive MSM.…”
Section: Hospital Wardmentioning
confidence: 99%
“…20 Less is known about college students' sexual behavior during the pandemic, although research with non-college student samples has shown a decrease in sexual activity and increase in dating app usage 21 since the implementation of social distancing guidelines. 18,[22][23][24][25][26][27][28][29][30] Engaging in substance use and sexual behavior to cope with COVID-19-related distress may not only increase students' risk for experiencing negative health outcomes (e.g., sexually transmitted infections), but also increase their risk for COVID-19 transmission and acquistion. [31][32][33] Changes in the health behaviors and psychosocial well-being of U.S. college students due to the pandemic may highlight the need for universities to adapt existing prevention and intervention services to address the mental and behavioral health needs of college students during the era of COVID-19.…”
mentioning
confidence: 99%